Pengaruh Pendampingan, Pembiayaan, dan Manajemen Keuangan terhadap Kualitas Hidup Keluarga Prasejahtera Produktif - Eka Dwi Pertiwi; Muhammad Hafiz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of mentoring, financing, and financial management programs carried out by Islamic financial institutions, especially BTPN Syariah, on the quality of life of productive underprivileged families in Pematang Siantar City. This study uses a quantitative approach with an associative method. The data analysis technique used is multiple linear regression, with a sample of 92 respondents who are active customers of BTPN Syariah. Data collection was carried out through a questionnaire that had been tested for validity and reliability. The results of the study indicate that partially, financing and financial management have a significant effect on quality of life, while mentoring does not show a statistically significant effect, although the relationship is positive. However, simultaneously, the third variable has a significant effect on the quality of life of productive underprivileged families, with a contribution of 64.1% (Adjusted R² = 0.641). This study offers theoretical and practical contributions by integrating three elements of Islamic economic empowerment in one comprehensive conceptual framework. These findings reinforce the importance of a holistic sharia-based approach in efforts to improve the economic welfare of marginalized communities. The implications of this study encourage Islamic financial institutions to not only focus on the financing aspect, but also strengthen educational and social functions through mentoring and increasing financial literacy.